PERPINDAHAN PANAS PADA AEROPONIK CHAMBER DENGAN APLIKASI ZONE COOLING - Eni sumarni (Jurnal Biofisika, 2013)
Energy cooling zone on aeroponics system for seed potato production in the lowland humid tropics can be analyzed based on the principle of heat transfer. Heat transfer occurring radiation, conduction, and convection. From the calculation of electrical load aeroponics system with cooling zone for seed potato production in lowland obtained that the cooling zone temperature of 10°C requires the greatest energy. The amount of electrical energy use on a daily average aeroponic chamber amounted to 0.132 kWh/m2 control, a temperature of 15°C for 0590 kWh/m2 and a temperature of 20°C for 0439 kWh/m2